Pengaruh Cara Belajar Terhadap Hasil Belajar Siswa Pada Mata Pelajaran Ekonomi Kelas IPS SMAN 1 Pendalian IV Koto - Vivi Andria; Khairi Murdy; Suparmi Suparmi (Jurnal Inovasi Pendidikan Ekonomi (JIPE), 2018)
This study aims to reveal the effect of learning methods on student learning outcomes in subjects in the Social Sciences class of SMA N 1 Pendalian IV Koto. This type of research is descriptive quantitative. The population is 197 people with a sample of 66 people using the Proportional random sampling technique. This research is quantitative research. The research instrument used was a questionnaire. Data analysis techniques using simple linear regression analysis. The results of the study showed that there were influences on how to learn about the results of learning economics. The magnitude of the contribution of learning methods to learning outcomes is equal to R2 0.501. This indicates that the way of learning contributes to student learning outcomes by 50.1%, while the rest is contributed by other factors that are not variables in this study.